Sistem Monitoring Lingkungan Rumah Cerdas berbasis Fog Computing dan nRF24l01 - Dwiki Nuridhuha; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Smart home technology is important to implement, but many smart devices can influence data exchanges between nodes, impacting communication performance between nodes or to the Internet on smart home devices. Therefore, the application of fog computing to handle Internet access constraints. While nRF24l01 can be applied to handle data exchange between nodes. The research consists of two sensor nodes, one sink/gateway node, and one fog node. The diffuser focuses on the performance measurements of nRF24l01 in the Fog computing environment, the parameters measured in the form of delay, throughput, packet loss and RTT (round trip-time) and time variation of delivery to the cloud. In this study the way of decomposition of performance is done by placing each node with each of the distance of multiples of 4 meters in the environmental conditions there is a barrier, and there is a barrier. From the test that has been done in the results can be the farthest delivery distance for the barrier is 28 meters, while without an obstacle of 44 meters. For delay performance, throughput, RTT (round trip-time) either without or there is a barrier and at any distance the performance value is not affected, but the performance of the packet loss more obstructions and away the data transmission will also increase the value of the packet loss. For variations of time to transfer data to the cloud either without or there is a barrier and at any distance do not undergo many changes.